Komitmen Pemerintah Kabupaten Jeneponto dalam Pengembangan Usaha Garam Rakyat (PUGAR) Sebagai Upaya Mensejahterakan Masyarakat - Ismail Dwi Saputra; Armin Arsyad; Muhammad Imran; Nurul Arifin (Universitas Muhammadiyah Sorong, 2026)
This paper analyzes the commitment of the Jeneponto Regency Government in implementing the People's Salt Business Development Program and its implications for the welfare of coastal communities. The main issue of this study is the limited capacity and consistency of local governments in supporting the sustainable implementation of the program. The purpose of this paper is to assess the role of local government institutions as a determining factor in the effectiveness of salt business development policies. The method used is a literature study by examining scientific sources, policy documents, and relevant previous research results. The results of the study show that there are still gaps in policy implementation, as reflected in the uneven distribution of assistance, weak technical assistance, low coordination between agencies, and limited understanding of salt production technology among farmers. These conditions have resulted in the program's objectives not being optimally achieved. The effectiveness of the People's Salt Business Development Program depends on strengthening local government governance, increasing the capacity of supporting resources, and expanding the active participation of coastal communities in all stages of program implementation.